1966
DOI: 10.1002/cjce.5450440401
|View full text |Cite
|
Sign up to set email alerts
|

The flow of suspensions through tubes: V. Inertial effects

Abstract: The behavior of particles undergoing Couette and Poiseuille flows at rates when inertial effects become significant was investigated. The rotation of rigid particles was similar to that in the Stokes flow regime, except for a drift of cylinders to limiting rotational orbits corresponding to the maximum energy dissipation. In Poiseuille flow, rigid particles migrated to an equilibrium radial position which depended on the density difference of two phases, the directions of sedimentation velocity and flow, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
142
0
2

Year Published

1969
1969
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(176 citation statements)
references
References 28 publications
32
142
0
2
Order By: Relevance
“…with GME are highly consistent with the experiments by Karnis et al [50]. This verifies that GME is competent to three-dimensional dynamic simulations.…”
Section: Three Dimensional Numerical Simulationsupporting
confidence: 90%
“…with GME are highly consistent with the experiments by Karnis et al [50]. This verifies that GME is competent to three-dimensional dynamic simulations.…”
Section: Three Dimensional Numerical Simulationsupporting
confidence: 90%
“…This effect, which has been verified by follow-up experimental [3][4][5] and theoretical 6,7 works, induces the migration of neutrally buoyant spherical particles in pipe flows to an annulus at approximately 0.6 of the a) Authors to whom correspondence should be addressed. Electronic addresses: guoqing.hu@imech.ac.cn and sunjs@nanoctr.cn.…”
Section: Introductionmentioning
confidence: 64%
“…The flow velocity and droplet deformation as well as the ratios of density, viscosity and the size between the droplets and the surrounding flow can also influence the equilibrium position. Karnis et al 5 have shown experimentally, when the Reynolds number (Re) is much less than unity, that highly deformable droplets in a Poiseuille flow migrate to the centerline if the viscosity ratio of the droplet and the surrounding flow λ is low (0.0002-4.8), whereas nearly spherical droplets with high λ suspended at a position halfway between the centerline and the channel wall behave like solid particles. Their results indicate that droplets can migrate in zero Re flow (without inertia) only if they deform; thus, the migration of a deformable droplet at non-zero Re is the result of competition between deformability and inertia.…”
Section: Introductionmentioning
confidence: 99%
“…In a pipe with radius R, particles are inertially focused into a ring with radius approximately 0.6R. Furthermore, particles with different sizes are focused at different rates and to rings with slightly different radii [11][12][13][14][15]. However, microfluidic channels are more readily built with a rectangular geometry, in which particles are inertially focused to either two or four stable equilibrium streamlines [6].…”
Section: Introductionmentioning
confidence: 99%